Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

3D Hexaporous carbon assembled from single-layer graphene as high performance supercapacitor - Yadav, Prasad; Banerjee, Abhik; Unni, Sreekuttan; Jog, Jyoti Prakash; Kurungot, Sreekumar; Ogale, Satishchandra (Chemsuschem, 2012)
Keywords: Electrochemistry; Energy storage; graphene; porous materials; Supercapacitors

Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor

Hollow Co0.85Se nanowire array on carbon fiber paper for high rate pseudocapacitor - Banerjee, Abhik; Bhatnagar, Sumit; Upadhyay, Kush Kumar; Yadav, Prasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2014)
A supercapacitor electrode is fabricated with Co0.85Se hollow nanowires (HNW) array, which is synthesized by wet chemical hydrothermal selenization of initially grown cobalt hydroxyl carbonate nanowires on conductive CFP. The dense self-organized morphology of Co0.85Se HNWs is revealed by scanning/transmission electron microscopy. The as-synthesized Co0.85Se HNWs possess high pseudocapacitive property with high capacitance retention and high durability. The areal capacitance value is seen to vary from 929.5 to 600 mF cm(-2) (60% retention) as the current density is increased from 1 to 15 mA cm(-2), an increase of a factor of 15. Based on mass loading, this corresponds to a very high gravimetric capacitance of 674 (for 2 mA cm(-2) or 1.48 Ag-1) and 444 Fg(1-) (for 15 mA cm(-2) or 11 A g(-1)) in a full-cell configuration with the Co0.85Se HNWs as cathode and activated carbon as anode (asymmetric configuration) promising results are obtained.
Keywords: asymmetric supercapacitor; carbon fiber paper; cobalt selenide; hydrothermal; pseudocapacitor; selenization

Oligomer-salt derived 3D, heavily nitrogen doped, porous carbon for Li-ion hybrid electrochemical capacitors application - Gokhale, Rohan; Aravindan, Vanchiappan; Yadav, Prasad; Jain, Srashti; Phase, Deodatta; Madhavi, Srinivasan; Ogale, Satishchandra (Carbon, 2014)
3D high surface area porous carbon is seen to form via self assembly of porous graphene sheets by direct pyrolysis of an oligomer salt tailored for the realization of molecular level activation. The oligomer salt was derived from 4-amino benzoic acid as the monomer by a facile free radical polymerization process. Incorporation of the functional groups (-COONa) eliminate the need for any external activating agents (KOH, ZnCl2, etc.) and also render high degree of sub-nanoscale homogeneity. This oligomer derived carbon (ODC) exhibits efficient performance in non-aqueous charge storage application namely Li-ion hybrid electrochemical capacitor (Li-HEC) owing to its high surface area, 3D interconnectivity and an appropriate pore size distribution. The Li-HEC fabricated with ODC based electrodes delivered a maximum energy density of similar to 63 Wh kg(-1) with spinel L4Ti5O12 as the anode. (C) 2014 Elsevier Ltd. All rights reserved.

Single-layer graphene-assembled 3D porous carbon composites with PVA and Fe3O4 nano-fillers: an interface-mediated superior dielectric and EMI shielding performance - Rao, B. V. Bhaskara; Yadav, Prasad; Aepuru, Radhamanohar; Panda, H. S.; Ogale, Satishchandra; Kale, S. N. (Physical Chemistry Chemical Physics, 2015)
In this study, a novel composite of Fe3O4 nanofiller-decorated single-layer graphene-assembled porous carbon (SLGAPC) with polyvinyl alcohol (PVA) having flexibility and a density of 0.75 g cm(-3) is explored for its dielectric and electromagnetic interference (EMI) response properties. The composite is prepared by the solution casting method and its constituents are optimized as 15 wt% SLGAPC and 20 wt% Fe3O4 through a novel solvent relaxation nuclear magnetic resonance experiment. The PVA-SLGAPC-Fe3O4 composite shows high dielectric permittivity in the range of 1 Hz-10 MHz, enhanced by a factor of 4 as compared to that of the PVA-SLGAPC composite, with a reduced loss by a factor of 2. The temperature dependent dielectric properties reveal the activation energy behaviour with reference to the glass transition temperature (80 degrees C) of PVA. The dielectric hysteresis with the temperature cycle reveals a remnant polarization. The enhanced dielectric properties are suggested to be the result of improvement in the localized polarization of the integrated interface system (Maxwell-Wagner-Sillars (MWS) polarization) formed by the uniform adsorption of Fe3O4 on the surface of SLGAPC conjugated with PVA. The EMI shielding property of the composite with a low thickness of 0.3 mm in the X-band (8.2-12.4 GHz) shows a very impressive shielding efficiency of similar to 15 dB and a specific shielding effectiveness of 20 dB (g cm(-3))(-1), indicating the promising character of this material for flexible EMI shielding applications.